Implications in selective sentinel node biopsy in internal mammary chain in breast cancer - Gonzales Espinosa, Claudia (2020)
Metastatic lymph node involvement is the most important prognostic factor in breast cancer. To know the degree of infiltration of the same involved progression-free survival, global survival and risk of early recurrence of the disease, and this in turn would help to know the adjuvant therapies that patients will receive. We present a case with a diagnosis of stage IB invasive ductal carcinoma of the left breast undergoing selective sentinel lymph node biopsy showing lymphocentellography, single migration to the internal mammary gland without access to it due to its retrocostal anatomical location, and axillary exploration and dissection were decided because this is what our protocol includes, based on cases like this, it forces us to carry out a review and update of the subject, and thus readjust our action protocols with the introduction of novel techniques in our country and the results of our first accumulated experiences. The internal mammary chain may be the only lymph node territory involved in selective sentinel lymph node biopsy and, in view of the results, it could obviate lymph node study at the axillary level when there is no clinical or radiological suspicion of involvement.